1980
DOI: 10.1021/bi00559a016
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic behavior of human and bacterial thymidylate synthetases and thymidylate synthetase-5-fluoro-2'-deoxyuridylate-5,10-methylenetetrahydrofolate complexes. Evidence for large conformational changes during catalysis

Abstract: The conformations of thymidylate synthetases from CCRF-CEM human leukemic cells and Lactobacillus casei were studied by hydrodynamic methods. Although the human enzyme has a molecular weight of 70 000--72 500, somewhat smaller than that of the L. casei enzyme, it has a larger Stokes radius and a lower sedimentation coefficient, indicating that the human enzyme is less spherical than the bacterial enzyme. Thymidylate synthetases from the human leukemic cells and the bacterial source both undergo substantial con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Danenberg and Danenberg (1979) have shown that FdUMP and CHrlLfolate binding to one catalytic site induced conformational changes that exposed the other catalytic site. Also, the formation of the ternary complex of thymidylate synthase with FdUMP and CH2-H4folate produced changes in the hydrodynamic properties of the enzyme, as measured by gel filtration and density gradient centrifugation, that were consistent with large conformational changes resulting in a more compact structure (Lockshin & Danenberg, 1980). The changes in absorption, fluorescence, and circular dichroic spectra that accompany ternary complex formation are consistent with conformational changes, though other interpretations are possible (Danenberg et al, 1974;Santi et al, 1974;Galivan et al, 1975;Donato et al, 1976; Manavalan et al, 1986).…”
mentioning
confidence: 72%
“…Danenberg and Danenberg (1979) have shown that FdUMP and CHrlLfolate binding to one catalytic site induced conformational changes that exposed the other catalytic site. Also, the formation of the ternary complex of thymidylate synthase with FdUMP and CH2-H4folate produced changes in the hydrodynamic properties of the enzyme, as measured by gel filtration and density gradient centrifugation, that were consistent with large conformational changes resulting in a more compact structure (Lockshin & Danenberg, 1980). The changes in absorption, fluorescence, and circular dichroic spectra that accompany ternary complex formation are consistent with conformational changes, though other interpretations are possible (Danenberg et al, 1974;Santi et al, 1974;Galivan et al, 1975;Donato et al, 1976; Manavalan et al, 1986).…”
mentioning
confidence: 72%
“…First, the difference in conformation between the free enzyme and the ternary complex can be easily observed by Sephadex gel filtration and high-speed centrifugation. The Stokes radius of TS from both human and bacterial sources was found to decrease by 3.5% (with a similar increase in sedimentation coefficient) upon ternary complex fromation, in spite of a 1.8% increase in molecular weight (161). Changes in conformation of this magnitude are normally associated with multisubunit allosterically controlled enzymes such as aspartate transcarbamylase (162).…”
Section: F Kinetics Of Ternary Complex Formation and Other Enzymologmentioning
confidence: 99%
“…However, in several ternary complexes, with both a nucleotide and a folate derivative bound, the asymmetric unit of crystalline E. coli TS is the dimer [3][4][5]. TS undergoes a considerable conformational change upon ternary complex formation [3,21]. The root mean square (rms) difference is 0.9 A between equivalent a-carbon positions for E. coli TS in the unliganded state and in a ternary complex with dUMP and 10-(3-propynyl)-5,8-dideazafolate [3].…”
Section: Structural Asymmetry Induced By Ligand Bindingmentioning
confidence: 99%